PENGGUNAAN METODE PQ4R UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS VIII SMP KHATULISTIWA JUNGKAT - Heriyanto, Heriyanto; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Abstract: This research aims to improve the reading skills of learning found the main problems in the news through methods preview, question, read, reflect, Recite, review the second semester of eighth grade students of SMP Equator Jungkat learning year 2012/2013. The method used is descriptive research procedure class measures consisting of 2 cycles. The results showed that the planning and implementation of learning has been implemented by teachers with appropriate and maximum. learning activities and motivation of students has increased in each cycle. Student learning outcomes also increased. Value of the average student in the first cycle is 63,76%, an increase on the second cycle of 83,33%.Â Keywords: Extensive Reading, Methods preview, question, read, reflect, recite, review